EFFECflVENESSOFTEACIllNG METHODS ON ENVIRONMENTAL HYGIENEPRACflCEAMONGALMAJIRAIINTSANGAYAIN KANO MUNICIPALLOCALGOVERNMENT AREA,KANO STATE, NIGERIA - HASSAN, A.I.; A.A. , SANUSI; H.U., USMAN (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2015)
This still was carried out to determine the effectiveness of demonstration. discussion and decillion teaching methods on environmental hygiene practice among almajirai in tsangaya in Kano Municipal LGA, Kano State, Nigeria. Pretest post-test control quasi experimental design was adopted for the study. The population of almajirai in this study was 117,688, a sample of 200 participants was drawn from four tsangaya schools in Kano Municipal LGA using multi[1]stage sampling procedure. A self-developed questionnaire named Almajirai’s Environmental Hygiene Practice Questionnaire (AEHPQ) was used as instrument for data collection and a reliability index of 0.85 was obtained using split-half method. Two hundred (200) questionnaires were administered at pre-test while; 198 were administered at post-test after 6 weeks treatment protocol to almafirai using demonstration, discussion and recitation teaching methods to almajirai in experimental groups and placebo to those in the control group. Lessons; on environmental hygiene was taught to almajirai in experimental groups using demonstration, discussion and recitation methods; and lesson on HIV/AIDS was taught to control group using lecture method. Mean and standard deviation scores were used to answer the research question and analysis of Covariance (ANCOVA) was used to test the null hypothesis. Alpha level 0/0.05 was used as criterion/or retaining or rejecting null hypotheses. The findings 0/ this study revealed that demonstration teaching method is the most effective method in eliciting positive environmental hygiene practice among almajirai in tsangaya in Kano Municipal, WA 0/Kano state, Nigeria. Based on the findings of this study, it was concluded that six weeks treatment protocols using demonstration teaching method is very effective in improving environmental hygiene practice among almajirai than discussion and recitation teaching methods. It was there/ore recommended among others those practical ways and strategies 0/ observing personal, environmental and food hygiene should be demonstrated and emphasized to almajirai in tsangaya to make the lesson workable in order to illicit positive change in their hygiene, behavior.